PERENCANAAN STRATEGIS DALAM PENDIDIKAN: PILAR UTAMA MENUJU TRANSFORMASI DAN INOVASI SD NEGERI 7 TALANG UBI - Winda Nopriani; Ria Adien; Parasih; Kasinyo Harto; Fitri Oviyanti (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the strategic planning implemented in SD Negeri 7 Talang Ubi to improve the quality of education and adaptation to changing times. The main focus of this study is the formulation of the vision, mission, objectives, and steps for implementing technology and character-based education strategies. In addition, this study also explores supporting and inhibiting factors in implementing strategies, including a SWOT analysis that includes the strengths, weaknesses, opportunities, and threats faced by the school. The method used in this study is descriptive qualitative with an observation approach, interviews, and analysis of school documents. Data were obtained from various sources, including the principal, teachers, school committee, and strategic planning documents. The results of the study indicate that the strategic planning of SD Negeri 7 Talang Ubi has been designed systematically through the evaluation of the vision and mission, preparation of medium and long-term plans, and implementation of periodic monitoring and evaluation. Implementing this strategy positively impacts improving the quality of learning, utilizing technology in education, and strengthening student character so that the school can transform into a superior and innovative educational institution. Keywords: Strategic planning, Education, Innovation, SWOT Analysis